2018
DOI: 10.1002/ldr.2964
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and microbial resistance in Brazilian soils under manure application

Abstract: Animal manure is commonly used in agriculture as fertiliser. This practice could represent, however, a risk of soil degradation through the accumulation of pharmaceutical residues or resistant microorganisms. Thus, 12 pharmaceuticals (11 antibiotics and 1 nonsteroidal anti‐inflammatory drug) were quantified in soil samples from 15 sites regularly fertilised with different animal manures (dairy cow, pig or poultry litter manure) and from forest sites in southern Brazil. This study (a) investigated the impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Although different applications of the DPSIR structure can be identified, to the best of our knowledge, no analysis has been conducted to organize and systematize studies focusing on the socioeconomic and environmental problems derived from the development of agricultural activities, which is important to consider given that agriculture plays an elementary role in this debate, as it uses approximately 50% of the planet's habitable land and consumes more than 60% of its fresh water volume [20]. Several studies have been conducted at a watershed scale that correlate aquatic ecosystem degradation and pollution to agricultural activities [21][22][23][24][25]. For example, agricultural land use is one of the main factors affecting nutrient status and sedimentation in streams [26], with its effects extending to fish community composition [27].…”
Section: Of 17mentioning
confidence: 99%
“…Although different applications of the DPSIR structure can be identified, to the best of our knowledge, no analysis has been conducted to organize and systematize studies focusing on the socioeconomic and environmental problems derived from the development of agricultural activities, which is important to consider given that agriculture plays an elementary role in this debate, as it uses approximately 50% of the planet's habitable land and consumes more than 60% of its fresh water volume [20]. Several studies have been conducted at a watershed scale that correlate aquatic ecosystem degradation and pollution to agricultural activities [21][22][23][24][25]. For example, agricultural land use is one of the main factors affecting nutrient status and sedimentation in streams [26], with its effects extending to fish community composition [27].…”
Section: Of 17mentioning
confidence: 99%
“…Resende et al [53] showed microbiological evidence of survival of AMR bacteria after biodigestion treatment of cattle manure, which could contaminate soils when applied as fertiliser. Camotti et al [52] found that each type of manure used as fertiliser in agricultural soils had a unique concentration of antibiotic residues and AMR genes, specific to the particular animal production system it originated from. Perhsson et al [50] and Kalter et al [42] identified inadequate human excreta management as an important human AMR-promoting factor in rural sites.…”
Section: Human Contributionmentioning
confidence: 99%
“…Anthropogenic drivers of AMR included intensive and non-intensive (small-scale/ extensive) animal production systems [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and agricultural practices [49,50,[52][53][54], such as the use of recycled or composted animal or human manure as fertiliser. Resende et al [53] showed microbiological evidence of survival of AMR bacteria after biodigestion treatment of cattle manure, which could contaminate soils when applied as fertiliser.…”
Section: Human Contributionmentioning
confidence: 99%
“…Urine and feces from users may contain considerable amounts of active residues. A study found that antibiotics and antibiotic-resistant genes exist in manure-fertilized soil and a nearby watershed ( Camotti Bastos et al, 2018 ). Thus, if urine is applied as fertilizer, then the occurrence and concentrations of antibiotics must be investigated for the safe usage of urine in agriculture.…”
Section: Introductionmentioning
confidence: 99%